1987
DOI: 10.3354/dao003159
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations on the toxicity of ammonia: effects on ventilation frequency, growth, epidermal mucous cells, and gill structure of rainbow trout Salmo gairdneri

Abstract: ABSTRACT. Juvenile rainbow trout Salmo gairdneri Rich. were experimentally exposed to 0.25 mg I-' of NH3 for 4 wk. This concentration lies between those causing acutely lethal and sublethal effects. At first, significant effects from the ammonia were recorded: greatly increased ventilation frequency, reduced food intake and an associated decrease in weight gain. Subsequently, the fish adapted considerably to the toxicant. Ventilation frequency decreased, although it remained above that of controls. Food was ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Due to the active flow of water across the gills, which is necessary for respiration, the risk that slimy secretions of the opercular epidermis will be continuously washed away is also much greater than in the case of general body skin. Exposure to various xenobiotics causes increased ventilatory movement by the operculum and a greater ventilation (water) volume which results in respiratory efficiency (Flis 1968a, b, Sausa & Meade 1977, Smart 1978, Hillaby & Randall 1979, Lang et al 1987). This aggravates the loss of slime d u e to sloughing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the active flow of water across the gills, which is necessary for respiration, the risk that slimy secretions of the opercular epidermis will be continuously washed away is also much greater than in the case of general body skin. Exposure to various xenobiotics causes increased ventilatory movement by the operculum and a greater ventilation (water) volume which results in respiratory efficiency (Flis 1968a, b, Sausa & Meade 1977, Smart 1978, Hillaby & Randall 1979, Lang et al 1987). This aggravates the loss of slime d u e to sloughing.…”
Section: Discussionmentioning
confidence: 99%
“…However, indiscriminate use of inorganic fertilizers including ammonium sulphate, which releases ammonia (both NH3 and NH,'), has created numerous environmental hazards for fish populations (Soderberg et al 1983, Lang et al 1987, Ram & Sathyanesan 1987, Sarkar 1991, Varadachari 1992, as these fertilizers contaminate neighbouring bodies of water, where they are mixed with run-off from agricultural fields. Although workers differ in their opinions regarding the optimal recommended dose of ammonium sulphate for aquaculture (Lakshmanan et al 1971, Jhingran 1983, Sarkar 1991, on the Indian subcontinent the quantity of this fertilizer used in actual practice quite often surpasses the dosages recommended for aquacultural as well as for agricultural purposes, thus caus-'Addressee for correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…This was associated with the appearance of mitotic cells. Epidermal hyperplasia was also reported in the skin of fish exposed to water polluted with manure or lead (Iger et al, 1988;Iger, 1992), as well as in the branchial epithelium of fish exposed to low water pH or nitrogenous waste products such as ammonia (Lang et al, 1987;Wendelaar Bonga et al, 1990). It may represent a general and adaptive response of external epithelia to stressors.…”
Section: The Epidermis and Its Filam Ent Cellsmentioning
confidence: 99%
“…However, most studies on the effects of pollutants on the body surface have been limited to the branchial or the intestinal epithelium (cf. Albassam et al, 1987;Lang et al, 1987; Burkhardt-Holm et al, revealed the formation of epidermal papillomas in fish exposed to polluted fresh water (Grizzle et al, 1984;Smith et al, 1989), the sensitivity of the skin to pollutants has received little attention. The skin of fish is a metabolically very active tissue, that quickly responds to stressors (Whitear, 1986;Iger et al, 1992), consisting of several cell types, in particular filament cells, mucous cells, sensory cells and chloride cells (Whitear, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…( Randall and Wright, 1987;Paust et al, 2011), , , , (Meade, 1985;Russo and Thurston, 1991) , (Lang et al, 1987), (McKenzie et al, 1993) (Ip et al, 2001). …”
Section: 서 론mentioning
confidence: 99%